Lipid-dense and pre-functionalized post-hydrolysis spent coffee grounds as raw material for the production of fatty acid methyl ester. (15th July 2021) - Quijote, Kristelle L.; Go, Alchris Woo; Agapay, Ramelito C.; Ju, Yi-Hsu; Angkawijaya, Artik Elisa; Santoso, Shella Permatasari
Highlights: Novel raw materials for biodiesel production from spent coffee grounds (SCG). Lipid-dense feedstock for the production of fatty acid methyl esters (FAME). Pre-functionalized post-hydrolysis SCG (PHSCG) with catalytic activity. In-situ FAME production using PHSCG without addition of catalyst. Functionalized PHSCG residues as solid acid catalyst for FAME synthesis. Abstract: In this study, lipid-dense post-hydrolysis spent coffee grounds (PHSCG), containing ~23 wt% lipid, was utilized as feedstock in the production of fatty acid methyl esters (FAME) via in-situ (trans)esterification (ISTE). The collected PHSCG were pre-functionalized (~0.86 mmol H + /g dried, lipid-free PHSCG) after sufficient drying of wet residues obtained from the dilute acid hydrolysis (DAH) of spent coffee grounds (SCG). Taguchi method and regression analysis were adopted in the optimization of the ISTE, with temperature, solvent-to-solid ratio (SSR), and reaction time, as the main factors investigated. An optimum yield of 19.47 ± 2.44 g FAME/100 g PHSCG, corresponding to ~96% conversion, could be achieved during ISTE in a batch reactor system. The ISTE of lipids in PHSCG were carried out without catalyst addition due to the inherent catalytic activity of the pre-functionalized PHSCG. Elemental and FT-IR analyses were conducted to determine the extent of the functionalization. The strong acid density of the material increased 21.5 times upon sufficient drying after DAH. Although, some of the functionalized material were solubilized during ISTE, the post-ISTE residue still had significant a strong acid site, 2.47 times of the native SCG, and exhibited appreciable activity when used as solid acid catalyst for the esterification of oleic acid and methanol while having good stability. The DAH and subsequent drying to induce simultaneous carbonization and sulfonation, may be adopted as a means of generating raw materials for biodiesel production from lipid-containing lignocellulosic residues like SCG.